The Role of Woman Preachers to Empower Torajan People Economy - Donald Samuel Slamet Santosa; Jony Oktavian Haryanto; I Wayan Ruspendi Junaedi; Dermawan Waruwu (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The Role of Woman Preachers to Empower Torajan People’s Economy. The aim of this research is to analyze the role of woman preachers to empower Torajan people’s economy. It used qualitative phenomenology research. The data were collected by interview and Focus Group Discussion to informants through purposive and snowball sampling. After that, the data were validated by technique, sources, and researchers triangulation. In terms of analysis, the data were analyzed using Miles and Hubberman’s method. Findings show that there are 3 main roles of woman preachers to empower Torajan people economy, namely role in context of increasing income, role in context of expenditure efficiency, and role in context of financial management. Those roles have strong relationship with the role of women in the family. The main challenge is the implementation of the roles in real life. Based on the results, it is recommended to strengthen the implementation of the woman preachers’ role.